SIMACoop: a Framework Application for the Governance of University Cooperation - Benmoussa, Khaoula; Laaziri, Majida; Khoulji, Samira; Mohamed Larbi, Kerkeb (Transactions on Engineering and Computing Sciences, 2017)
The management of the cooperation is the process of establishing and ensuring the continuation of constructive and productive relations, consistent with partners. It requires the allocation of time and resources needed to maintain the existing partnership and communicate regularly with partners, and to enable all parties to track the functioning of the partnership. Management system applies to all categories of partners with universities, which include governments, international funders, local authorities, chambers of Commerce and Industry, consulates and embassies, etc. The areas of partnership with universities include academic and research fields but also institutions management to contribute to community service, implement joint projects, provides common services, share and exchange information, implementation joint activities, etc. For a good piloting of the cooperation, an information system becomes an obligatory requisite to manage better partnerships, to evaluate the research performance and to establish a sound policy for the development of the institution relationship. Based on the use of an effective application developed by aAbdelmalek Essaâdi University (UAE) team, SIMAcoop is a monitoring system aimed at supporting the governments and universities plan of cooperation, partnership and students exchange programs. The objective of SIMAcoop is to enhance communication, collaboration and integration among universities and their partners, to improve in performance management, strategic planning, and monitoring and evaluation by leveraging the use of spatial data. This emphasis on flexibility to align to national priorities will strengthen mainstream data collection and analysis procedures and, therefore, improve the quality of data reported top management of institutions.